2021
DOI: 10.18087/cardio.2021.8.n1638
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury in COVID-19 patients is associated with the thickness of epicardial adipose tissue

Abstract: Aim    High sensitive troponin (hs-TnI) levels may increase secondary to Coronavirus disease-2019 (COVID-19), and this increase is associated with cardiovascular mortality in COVID-19 patients. Epicardial adipose tissue (EAT) is associated with myocardial injury directly as a reservoir tissue for coronavirus, and indirectly through mediators it secretes as an apocrine gland. We aimed to evaluate the relationship between myocardial injury secondary to COVID-19 infection and EAT thickness.Material and methods   … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Typical are interstitial ground glass opacities with or without consolidation, reticular pattern with air bronchogram, then fibrosis, pleural thickening and effusion as well as nodules with halo sign, lymphadenopathy, and pericardial effusion [45]. Perincek et al [46] in their study showed that a cutoff value of 5.5 for global CT score (depending on the degree of lung lobe involvement, in the possible range of 0-25) predicted in-hospital mortality with 74% sensitivity and 73% specificity, and global CT score was correlated with levels of CRP, D-dimer, natriuretic peptide and procalcitonin [47]. In Table 1 commonly used CT score in patients with COVID-19 pneumonia is presented.…”
Section: Covid-19 Imaging In Ct and Cmrmentioning
confidence: 98%
“…Typical are interstitial ground glass opacities with or without consolidation, reticular pattern with air bronchogram, then fibrosis, pleural thickening and effusion as well as nodules with halo sign, lymphadenopathy, and pericardial effusion [45]. Perincek et al [46] in their study showed that a cutoff value of 5.5 for global CT score (depending on the degree of lung lobe involvement, in the possible range of 0-25) predicted in-hospital mortality with 74% sensitivity and 73% specificity, and global CT score was correlated with levels of CRP, D-dimer, natriuretic peptide and procalcitonin [47]. In Table 1 commonly used CT score in patients with COVID-19 pneumonia is presented.…”
Section: Covid-19 Imaging In Ct and Cmrmentioning
confidence: 98%
“…Myocardial edema and necrosis of myocardial cells and connective tissue interstitium represent this viral-induced myocarditis. The cell-mediated auto-immune response caused by the virus can also lead to myocarditis [27]. Epicardial fat is linked with myocarditis, by acting as a reservoir for the COVID-19 virus and by the release of adipokines.…”
Section: Myocarditismentioning
confidence: 99%
“…In a study by Özer et al [27], the computerized tomography (CT-Scan) technique was used to evaluate the thickness of epicardial fat. Epicardial fat acts as a reservoir of coronavirus and contributes to cytokinemediated myocardial inflammation among patients with COVID-19.…”
Section: Computerized Tomography (Ct-scan)mentioning
confidence: 99%
“…In previous studies, it has been shown that increased EAT volume is associated with both decreased lung function in healthy individuals and increased disease severity in patients with chronic lung disease [ 10 , 11 ]. Recent studies have advanced the potential role of EAT as a risk factor for myocardial inflammation in COVID-19 patients [ 12 , 13 ]. Recently, EAT has also been proposed to be independently associated with the extent of pneumonia and adverse outcomes in patients with COVID-19 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%